2020
DOI: 10.3168/jds.2019-17698
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding a high-fiber or high-starch pellet at two daily allocations on feed intake patterns, rumen fermentation, and milk production of mid-lactation dairy cows

Abstract: The objective of this experiment was to determine the effect of pellet type and feeding amount on feeding behavior, dry matter intake, rumen fermentation, and milk production of lactating dairy cows. An experimental diet was formulated to provide an adequate amount of nutrients to a 650-kg cow producing 40 kg of milk per day, with a portion of the diet removed as a highfiber (33.2% neutral detergent fiber; F) or high-starch (56.8% starch; S) pellet. Pellets were fed at a low (1 kg; L) or high (3 kg; H) amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Se evidenciaron mayores porcentajes de proteína en los tratamientos T2 y T3 y para el NUL el T2 mostró la más alta concentración (Cuadro 2). El consumo de materia seca de los ensilajes el tratamiento T4 fue mayor, seguido del T3 y finalmente del T2 respectivamente (Cuadro 3), estos resultados pueden estar relacionados al contenido de FDN de cada uno de los tratamientos, pues como se ha indicado, el consumo va a depender del volumen estructural de la dieta y por tanto del contenido de fibra detergente neutro (FDN) (Haisan and Oba, 2020). Los resultados de producción de leche, sólidos totales y porcentaje de grasa en la leche se pueden atribuir al bajo aporte de materia seca (MS) de cada uno de los ensilajes (Cuadro 1); en términos de materia seca, la suplementación diaria de ensilado fue de 0,73 kg/d para el T2 (Bellucia grossularioides), 0,89 kg/d para el T3 (Crescentia cujete) y 0,63 kg/d para el T4 (Mangifera indica), lo cual, en promedio, equivale a una suplementación del 0,15 % del peso vivo en materia seca, por lo tanto, se puede inferir que la producción diaria de leche, sólidos totales y porcentaje de grasa en la leche no fueron alteradas debido a la baja suplementación.…”
Section: Resultados Producción Y Composición De La Lecheunclassified
See 1 more Smart Citation
“…Se evidenciaron mayores porcentajes de proteína en los tratamientos T2 y T3 y para el NUL el T2 mostró la más alta concentración (Cuadro 2). El consumo de materia seca de los ensilajes el tratamiento T4 fue mayor, seguido del T3 y finalmente del T2 respectivamente (Cuadro 3), estos resultados pueden estar relacionados al contenido de FDN de cada uno de los tratamientos, pues como se ha indicado, el consumo va a depender del volumen estructural de la dieta y por tanto del contenido de fibra detergente neutro (FDN) (Haisan and Oba, 2020). Los resultados de producción de leche, sólidos totales y porcentaje de grasa en la leche se pueden atribuir al bajo aporte de materia seca (MS) de cada uno de los ensilajes (Cuadro 1); en términos de materia seca, la suplementación diaria de ensilado fue de 0,73 kg/d para el T2 (Bellucia grossularioides), 0,89 kg/d para el T3 (Crescentia cujete) y 0,63 kg/d para el T4 (Mangifera indica), lo cual, en promedio, equivale a una suplementación del 0,15 % del peso vivo en materia seca, por lo tanto, se puede inferir que la producción diaria de leche, sólidos totales y porcentaje de grasa en la leche no fueron alteradas debido a la baja suplementación.…”
Section: Resultados Producción Y Composición De La Lecheunclassified
“…Por el contrario, donde los valores son menores como en el estudio realizado con los ensilados (T2, T3, T4) indicaría una mejor relación del balance y sincronización entre la energía y proteína que ingresan al rumen (Zhang et al, 2020). En este sentido, los animales que recibieron una dieta energética proveniente del tratamiento a base de ensilaje Mangifera indica, mostraron un menor nivel de nitrógeno ureico en leche, indicando un mayor aporte de energía (Haisan and Oba., 2020). Respecto a los niveles de betahidroxibutirato (BHB), no se encontraron diferencias, arrojando parámetros normales para cada uno de los tratamientos evaluados, considerándose aceptables de 0,1 a 0,6 mmol /L (Guevara et al, 2016).…”
Section: Resultados Producción Y Composición De La Lecheunclassified
“…The circadian changes in pH values of all cows showed the same pattern as mentioned above. These changes could be explained by the nutritional composition of PMR, which has a larger effect on rumen fermentation digesta and the risk of SARA than AMS pellets [ 7 , 13 ]. Furthermore, although the cows randomly received the AMS pellets, the SEM for ruminal pH was fairly small.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study on the relationship among the starch levels of AMS pellets, ruminal pH, ruminal LPS concentration, and plasma metabolite concentrations. Recent studies have found that increased NDF proportion or forage-to-concentrate ratio in PMR resulted in a decreased duration of ruminal pH below 5.8 [ 7 ] or an increase in the minimum ruminal pH [ 13 ]. The mechanism of PMR nutritional composition, which affects metabolite variables, especially plasma acute phase proteins, needs to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…A limited amount of nutrients should be provided with starchy grains due to their acidogenic effect. Otherwise a high amount of pelleted concentrates, (>6 kg/d per cow) independently from the carbohydrate source (starch or high digestible fibre) offered in automatic milking systems, decreased the time the rumen remained below 5.8 pH and increased DMI (Haisan and Oba 2020).…”
Section: How To Feed 20t Cowsmentioning
confidence: 99%